2005
DOI: 10.1080/13691050412331321294
|View full text |Cite
|
Sign up to set email alerts
|

Identity experience among progressive gay Muslims in North America: A qualitative study within Al‐Fatiha

Abstract: This qualitative study aims to document the identity experience of progressive gay Muslim men in a North American context. Six in-depth interviews, supplemented with participant observation, were conducted of gay Muslim men who attended an international conference for lesbian, gay, bisexual, transgendered, and questioning (LGBTQ) Muslims. For progressive gay Muslims such as these, a Muslim identity appears three-dimensional (religious, ethno-cultural, and color) when integrated with a gay identity. As a religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 8 publications
0
72
0
1
Order By: Relevance
“…This article focuses on queer Muslims' struggle for due recognition from mainstream Australian society, Australia's abidingly homophobic Muslim communities, and from Australia's overwhelmingly secular queer communities wherein 71.5% of individuals claim 'no religion' (Pitts et al 2006). In contrast to previous studies on queer Muslims by Yip (2003Yip ( , 2004Yip ( , 2005 and Siraj (2006) in the UK and Minwalla et al (2005) in the USA, rather than engaging with queer Muslims on an ethnographic level, this article offers a political engagement with contemporary issues of identity and belonging confronting queer Muslims in an age of ideological warfare. My approach here is Marxist, a tradition that numerous scholars of Islam and the Muslim majority world have worked within, or alongside.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This article focuses on queer Muslims' struggle for due recognition from mainstream Australian society, Australia's abidingly homophobic Muslim communities, and from Australia's overwhelmingly secular queer communities wherein 71.5% of individuals claim 'no religion' (Pitts et al 2006). In contrast to previous studies on queer Muslims by Yip (2003Yip ( , 2004Yip ( , 2005 and Siraj (2006) in the UK and Minwalla et al (2005) in the USA, rather than engaging with queer Muslims on an ethnographic level, this article offers a political engagement with contemporary issues of identity and belonging confronting queer Muslims in an age of ideological warfare. My approach here is Marxist, a tradition that numerous scholars of Islam and the Muslim majority world have worked within, or alongside.…”
Section: Introductionmentioning
confidence: 76%
“…Although there have been a number of cultural, historical and theological studies of Islam and same-sex relationships and eroticism (Abraham 2008;AbuKhalil 1997;Duran 1993;El-Rouayheb 2005;Haqq 2000;Jamal 2001;Kugle 2003;Massad 2002;Murray and Roscoe 1997;Rouhani 2007;Schmitt and Sofer 1992), to date, only a handful of social scientific studies have been conducted with queer Muslims in the so-called 'West'-that is, Europe and its settler colonies. In the Netherlands, El Karka and Kursun (2002) studied queer Muslim youths; in the UK, Yip (2003Yip ( , 2004Yip ( , 2005 completed an extensive study of largely South Asian queer Muslims, whilst Siraj (2006) completed a smaller British study; in the USA, Minwalla et al (2005) undertook a small ethnographic study of members of the queer Muslim group Al-Fatiha, and in Australia, Hammoud-Beckett (2007) produced a small Foucauldian study.…”
Section: Introductionmentioning
confidence: 99%
“…Halstead and Lewicka described how homosexuality in Islamic cultures is largely devoid of the politicization that forms the basis of the Western gay movement and, thus, the notion of a gay identity does not exist for Muslims outside of Western cultures. While Western critics may point out the rise of visible gay and lesbian movements in parts of the Middle East and Asia, the notion that for Muslims "gay identity" does not exist outside of Western culture was recently supported by Minwalla, Rosser, Feldman, and Varga's (2005) study of Muslims in North America, and by Boellstorff's (2005) study of Indonesian Muslims. However, the Muslim who is homosexual, lives in a Western society and by self-identifying as "gay" may come to experience a similar identity conflict between their sexual orientation and their religious beliefs as experiences by many of his or her Western Christian or Jewish brethren (Minwalla et.…”
Section: Focus On Western Religious Experiencementioning
confidence: 99%
“…Bailey reported that this verse may have been amended to the original codes through a later edition. Minwalla, Rosser, Feldman, and Varga (2005) stated that the story of Lot (or Lut) in Sodom along with the interpretation of "might know them" referred to same-sex behaviors led to the obliteration of Lut's people.…”
Section: Influence Of Religion On Gay and Lesbian Identitymentioning
confidence: 99%